Study Literature of The Influence of The Development Social Skills Elementary School Students to The Competence Pedagogic Teacher on Social Science Learning - Mahardika, Sofyan Nur; Sa'ud, Udin Syaefudin (International Conference on Elementary Education, 2020)
The purpose of this paper is to discuss the role of teacher pedagogical competence in developing students' social skills in social science learning. To achieve this goal, the method used is the study of literature describing the social skills of elementary students based on several experts and based on supporting reference studies. The focus of the discussion in this study is on social skills and teacher pedagogical competencies . Social skills are one of the skills students must possess. But in reality, there are still many problems related to the development of these social skills in schools, especially in social studies. This results in a low level of student social skills and a lack of teacher pedagogical competence in social studies learning at school. There are several ways that can be used by teachers in an effort to instill social skills in students. One of them is by integrating it with classroom learning activities. However, to carry out good social studies activities, teachers must also have good pedagogical competencies. so, social skills can be well taught to students and achieve learning goals